Um novo periódico «Information Development: The International Journal for Librarians, Archivists and Information Specialists - Nunes, Luis Filipe de Abreu (Cadernos BAD, 1984)
Um novo periódico «Information Development: The International Journal for Librarians, Archivists and Information Specialists